Acute complicated appendicitis caused by an ingested toothpick – A case report. (March 2022) - Lloyd, A.J.; Abd Elwahab, S.M.; Boland, M.R.; Elfadul, A.; Hill, A.D.K.; Power, C.
Abstract: Introduction and importance: Acute appendicitis is one of the most common presentations to the emergency department, particularly in young adults. A combination of clinical suspicion, inflammatory blood markers and imaging modalities such as ultrasound and CT are used for its definitive diagnosis. Early detection and intervention are paramount to reduce morbidity and mortality. Laparoscopic appendicectomy is the current gold standard in the management of appendicitis, especially if complicated according to EAES guidelines. There are few documented cases in the literature of acute appendicitis secondary to foreign body ingestion. On account of this, there are currently no guidelines for its management. Our literature review highlights the importance of surgical management of foreign body acute appendicitis. Case presentation: This case report describes the rare presentation of acute complicated appendicitis caused by an ingested toothpick in a 64 year old woman. The patient was admitted with a 3 day history of lower abdominal pain, localizing to the right iliac fossa with raised inflammatory markers. CT imaging reported acute complicated appendicitis. Laparoscopic appendicectomy was performed during which a toothpick was seen protruding through the appendiceal wall. Post operatively the patient was treated with IV antibiotics for 5 days prior to discharge. Clinical discussion: Due to the rare nature of foreign body appendicitis there are no specific guidelines on the respective surgical approach. A literature review showed that in the setting of foreign body appendicitis, surgical intervention is paramount with no scope for conservative management. Conclusion: Surgical approach is based on the clinical judgement and skillset of the operating surgeon. Highlights: Remember foreign body ingestion as a cause of appendicitis Management of foreign body appendicitis is surgical intervention. Open vs laparoscopic approach depends on the surgeons clinical judgement, preference and skillset.